Empowering Tette Chips MSMEs Through Social Media Based Digital Marketing Strategies in Lebbek Village, Pakong District, Pamekasan Regency - Mawaddah, Mawaddah; Winda Lidiyana; Arifah Nuril Maufiroh; Sri Wahyuni; Nuri Silviati; Febriyanti Dwi Wulandari (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
The Tette Nira Chips MSME in Lebbek Village has significant growth potential, offering unique flavors that reflect the richness of local culture and natural resources. However, significant challenges such as limited market access, low digital literacy, and the inability to manage modern promotions hinder their growth. This study aims to explore empowerment strategies through social media-based digital marketing. By utilizing platforms such as WhatsApp Business, Facebook, TikTok, and Instagram, MSMEs can increase the visibility and competitiveness of their products. The empowerment program includes creating dedicated social media accounts, product photography training, and promotional assistance through stories and feed features. Despite challenges such as limited internet access and limited use of marketing features, the training conducted by KKN students demonstrated a significant increase in MSMEs' knowledge of digital marketing strategies. The results of this study are expected to provide insights for developing more effective marketing strategies for Tette Nira Chips products and support the growth of MSMEs in Lebbek Village.